2015
DOI: 10.1186/s40462-015-0055-4
|View full text |Cite
|
Sign up to set email alerts
|

Step by step: reconstruction of terrestrial animal movement paths by dead-reckoning

Abstract: BackgroundResearch on wild animal ecology is increasingly employing GPS telemetry in order to determine animal movement. However, GPS systems record position intermittently, providing no information on latent position or track tortuosity. High frequency GPS have high power requirements, which necessitates large batteries (often effectively precluding their use on small animals) or reduced deployment duration. Dead-reckoning is an alternative approach which has the potential to ‘fill in the gaps’ between less r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
176
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(177 citation statements)
references
References 107 publications
1
176
0
Order By: Relevance
“…To accurately measure biomechanics and movement ecology of echidnas on a fine scale, we used a combination of accelerometer and GPS units. This combination has been used previously (Bidder et al, 2015) and can offer a unique perspective on animal movement. Each measurement method has potential advantages and disadvantages, as our study has demonstrated.…”
Section: Comparisons Of Accelerometer and Gps Estimatesmentioning
confidence: 99%
“…To accurately measure biomechanics and movement ecology of echidnas on a fine scale, we used a combination of accelerometer and GPS units. This combination has been used previously (Bidder et al, 2015) and can offer a unique perspective on animal movement. Each measurement method has potential advantages and disadvantages, as our study has demonstrated.…”
Section: Comparisons Of Accelerometer and Gps Estimatesmentioning
confidence: 99%
“…The latter often employs high-resolution spatial and temporal information to analyse the behaviour of animals. Depending on the sensors used, aspects such as energy expenditure, behaviour, location, speed, heart rate and temperature are monitored [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Future work may seek to compare the performance of (or augment) animal-attached VIO motion tracking with previously described magnetometer, accelerometer, and GPS-based dead-reckoning methods (e.g. [93]) in a range of environments. For example, under dense vegetation where the performance of GPS can deteriorate, VIO could offer significant advantages [38,94].…”
Section: Discussionmentioning
confidence: 99%